2021
DOI: 10.3390/genes12101482
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Related Phenotypes in a Bipolar Sample: Genetic Underpinnings

Abstract: Suicide in Bipolar Disorder (BD) is a relevant clinical concern. Genetics may shape the individual risk for suicide behavior in BD, together with known clinical factors. The lack of consistent replication in BD may be associated with its multigenetic component. In the present contribution we analyzed a sample of BD individuals (from STEP-BD database) to identify the genetic variants potentially associated with three different suicide-related phenotypes: 1) a feeling that the life was not worth living; 2) fanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 117 publications
(129 reference statements)
1
4
0
Order By: Relevance
“…This evidence is in line with previous items of research that have reported an increased suicidality risk in ASD populations [ 58 , 95 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. The association between ASD and suicidality has long been discussed, and a number of factors contributing to the correlation have been identified.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This evidence is in line with previous items of research that have reported an increased suicidality risk in ASD populations [ 58 , 95 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. The association between ASD and suicidality has long been discussed, and a number of factors contributing to the correlation have been identified.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, as reported by multiple twin and family studies, genetics may be one of the variables influencing the risk of suicide [ 58 ]. In particular, the genetic component for suicide also appears to be shared with the inheritance of psychiatric disorders [ 59 , 60 ], and a recent genome-wide association study revealed an intriguing correlation between suicide attempts and depressive symptoms, neuroticism, schizophrenia, insomnia, and major depressive disorder [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our search revealed thirty‐one GWAS studies for SITB (Table 1), of which nineteen were focused exclusively on suicidal behavior (SA/SD). Some studies which included SI did so by considering continuous suicidality scales ranging from no suicidality to SI to SA (i.e., no reference group; Lybech et al, 2021; Schosser et al, 2011; Strawbridge et al, 2019; Zai et al, 2015; Zai et al, 2021), and only six studies assessed SI independently of suicidal behavior (Brick et al, 2019; Campos et al, 2020; Kimbrel et al, 2018; Mullins et al, 2014; Polimanti et al, 2021; Shen et al, 2020). In most cases, the large sample size needed for GWAS required a combination of multiple cohorts for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of all identified GWAS published to date, nine (Bani‐Fatemi et al, 2016; Lybech et al, 2021; Mullins et al, 2019; Perlis et al, 2010; Rao et al, 2020; Schosser et al, 2011; Willour et al, 2012; Zai et al, 2015; Zai et al, 2021) focused on specific diagnostic groups, such as bipolar disorder (BD) and major depressive disorder (MDD), with some including multiple psychiatric disorder groups assessed separately. There was one GWAS focused on SI in youth (Brick et al, 2019), with no GWAS reports on suicidal behavior in youth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation